Velocity dependence of sliding friction on a crystalline surface - Apostoli, Christian; Giusti, Giovanni; Ciccoianni, Jacopo; Riva, Gabriele; Capozza, Rosario; Woulaché, Rosalie Laure; Vanossi, Andrea; Panizon, Emanuele; Manini, Nicola (Beilstein Journal of Nanotechnology, 2017)
We introduce and study a minimal 1D model for the simulation of dynamic friction and dissipation at the atomic scale. This model consists of a point mass (slider) that moves over and interacts weakly with a linear chain of particles interconnected by springs, representing a crystalline substrate. This interaction converts a part of the kinetic energy of the slider into phonon waves in the substrate. As a result, the slider experiences a friction force. As a function of the slider speed, we observe dissipation peaks at specific values of the slider speed, whose nature we understand by means of a Fourier analysis of the excited phonon modes. By relating the phonon phase velocities with the slider velocity, we obtain an equation whose solutions predict which phonons are being excited by the slider moving at a given speed.
Keywords: atomic-scale friction; contact; dissipation; friction; nanotribology; phonons; velocity dependence